Calcified Chronic Subdural Hematoma: A Case Report - Chaulagain, Dipak; Munakomi, Sunil; Bhattarai, Binod; Shah, Sashi Bhushan (Eastern Green Neurosurgery, 2022)
Calcified Chronic Subdural Hematomas (CCSDH) are uncommon subdural hematoma (CSDH). It is believed that they account for between 0.3% and 2.7% of all CSDH. Increased intracranial pressure, seizures, and nerve damage are all possible clinical manifestations. We present the case of a 65-year-old man who, three months before he began experiencing motor function issues in his left limbs, had a history of a fall injury. In the right cerebral hemisphere, CT scans revealed a sizable subdural collection surrounded by a calcified inner membrane. The patient's clinical and radiological symptoms improved after this collection was successfully and totally eliminated. Subdural hematomas rarely calcify. This odd lesion was surgically removed, and the patient's symptoms progressively and totally subsided, restoring his neurological state. Based on published examples and our personal experience, we feel that surgical therapy in symptomatic patients is important and viable, often resulting in patient improvement.